Interactions Between Bt-Bioinsecticides and Podisus nigrispinus (Dallas) (Hemiptera: Pentatomidae), a Predator of Plutella xylostella (L.) (Lepidoptera: Plutellidae) - Magalhães, G. O. [UNESP]; Vacari, A. M. [UNESP]; DE Bortoli, C. P. [UNESP]; Pomari, A. F.; DE Bortoli, S. A. [UNESP]; Polanczyk, R. A. [UNESP] (Springer Nature, 2015)
Bioinsecticides are being increasingly used to protect vegetable crops against herbivores, but data on the side effects of such strategy on the third trophic level are still required. We investigated the influence of the Bacillus thuringiensis subsp. kurstaki HD-1 strain and of the commercial bioinsecticide Agree® on the biological aspects of the predator Podisus nigrispinus (Dallas) (Hemiptera: Pentatomidae) when feeding on Plutella xylostella (L.) (Lepidoptera: Plutellidae)-infected larvae. On average, infected larvae were consumed more often than the non-infected larvae throughout the predator nymphal development, and no effect on nymph survival was observed. Population growth parameters (R0, rm, and λ) resulting from the fertility life tables did not differ among treatments. The results led to the conclusion that P. nigrispinus can be used in combination with the product Agree® or the strain HD-1 for the control of P. xylostella. The combined use of these control agents helps to maintain the balance of the ecosystem and contributes for the production of food for healthy human consumption.
Keywords: Biological control; food security; insect biology; microbial control; sustainable pest management